A Tungsten Nitride‐Based O2 Self‐Sufficient Nanoplatform for Enhanced Photodynamic Therapy against Hypoxic Tumors. Issue 6 (7th March 2019) - Wang, Shi‐Bo; Zhang, Cheng; Liu, Xin‐Hua; Chen, Zhao‐Xia; Peng, Si‐Yuan; Zhong, Zhen‐Lin; Zhang, Xian‐Zheng
Abstract: The hypoxic microenvironment of tumors is a natural barrier to photodynamic therapy (PDT) and closely related to the tumor metastasis. Here, chlorine e6 (Ce6) decorated tungsten nitride nanoparticles (WN NPs) with a folic acid (FA) modification are fabricated to produce FA‐WN‐Ce6 (FWC) NPs for enhanced photodynamic therapy against hypoxic tumors. FWC NPs can efficiently accumulate in tumor sites via FA‐mediated specific tumor targeting. With 630 nm laser irradiation, the WN in FWC can act as a photocatalyst for water splitting to provide oxygen (O2 ), which significantly improves the reactive oxygen species (ROS) generation ability of Ce6 in hypoxia and achieves an enhanced PDT effect both in vitro and in vivo. In addition, the O2 produced by FWC NPs can also weaken the hypoxia level in tumor tissue, and thus reduces the invasion and metastasis of tumor cells. Additionally, no apparent systemic toxicity is observed after the treatment of FWC NPs. Overall, these results indicate the great potential of FWC NPs as safe and effective nanoplatform for both enhanced tumor PDT and against metastasis. Abstract : A chlorine e6 (Ce6)‐decorated tungsten nitride (WN) nanoparticle with a folic acid (FA) modification (FA‐WN‐Ce6, FWC) is developed for enhanced photodynamic therapy (PDT) against hypoxic tumor. The WN content of FWC acts as a photocatalyst for water splitting to provide oxygen, which enhances reactive oxygen species (ROS) generation in hypoxic tumors and also reduces metastasis.